IMPLEMENTASI SURAT EDARAN MAHKAMAH AGUNG (SEMA) NOMOR 4 TAHUN 2010 BAGI HAKIM DALAM MEMUTUS PERKARA NARKOTIKA - Rachmat Sumantri (2022)
Narcotics is the biggest threat to the nation of Indonesia at this time. Indonesia is one of the state emergency drugs to see the high level of prevalence of drug each year. Circulation and drug abuse is a national problem that is viewed seriously by the government, as it can cause damage to the morale of the nation. Therefore the government is to give attention to the handling of drug abuse. For drug abuse prevention efforts are needed that are integrated and komprenhensif which includes preventive, repressive, therapy and rehabilitation. One of the efforts the Government is to make Regulations With the Chairman of the Supreme Court of the Republic of Indonesia, the Minister of Law and Human Rights Republic of Indonesia, Minister of Health of the Republic of Indonesia, Minister of Social affairs of the Republic of Indonesia, the Prosecutor general of the Republic of Indonesia, Head of the State Police of the Republic of Indonesia, Head of the National Narcotics Agency of the Republic of Indonesia Number: 01/Pb/Ma/Iii/2014, Number: 03 2014, Number : 11/2014, Number : 03 2014, Number : Per-005/A/Ja/03/2014, Number : 1 Year Of 2014, The Number : Joint Regulations/01/Iii/2014/BNN About The Handling Of Narcotic Addicts And Victims Of Drug Abuse In Institutions Of Rehabilitation. In addition to Regulation, the Supreme Court also issued a Circular of the Supreme Court (SEMA) No. 4 of 2010 that is intended for the Judges as a guideline in examining and deciding the case of narcotics to addicts and victims of abusers of narcotics so sentenced medical rehabilitation and social rehabilitation as determined in the SEMA No. 4 of 2010